Evaluation of National Health Insurance Program Implementation in Jakarta Province, Indonesia - Evi Susanti Sinaga; Ika Rahma Ginting; Rina K Kusumaratna; Tiara Marthias (Center for Health Policy and Management, 2021)
The implementation of National Health Insurance in several regions in Indonesia faces challenges, such as health service providers, health insurance management , and the community. The outcome that occurs may vary depending on the implementation of different aspects of governance, equity or social justice, and aspects of service quality. Therefore, research was conducted by evaluating the implementation of the national health insurance in DKI Jakarta Province. The evaluation is carried out based on the 2019 JKN road map target indicators, grouped into three aspects: including governance, achievement of equal distribution of health services (equity), and quality of service. This research used a mixed-methods design that combined the approach of quantitative and qualitative elements. Quantitative data were collected from secondary data from Health Social Security Agency (BPJS Kesehatan), the National Social Security Council Monitoring and Evaluation System (Sismonev DJSN). The qualitative data comes from in-depth interviews with selected informants using the purposive sampling technique. The result was that DKI Province had achieved the JKN membership target. There are still JKN participants who are inactive / in arrears from participants in the government and private wage-earning segments. Health facilities and human health resources have met the standards, but related to the package of benefits for heart diseases services, the availability of cardiac specialists and cath lab facilities has not been evenly distributed, especially in the Seribu Islands. Patient preferences in choosing the desired health service resulted in implementing a tiered referral system and back-referral still having problems in health facilities.